Leadership Practices of An Award Winning Head Tecaher in a Remote primary School in Sarawak, Malaysia - Yap, Mary Kain Ching (2016)
Poor school performance seems to be prevalent in small rural school districts because of factors such as low income, poverty, scarcity of resources, and the unavailability of highly qualified teachers. The problem of ineffective school leadership and poor retention of high-quality teachers have been an ongoing problem in Malaysia affecting thousands of the most needy and disadvantaged primary school students. The purpose of the study was to describe the leadership practices of an award winning head teacher and to find out what it was about his leadership that had enabled him to beat the odds. The turning point for this school, leading to its amazing transformation came in 2000 when this head teacher was posted there. Unhappy with the school's UPSR low passing before 2000, he vowed to turn around the school. Within three years, the Head Teacher successfully led the school to the top position in the district. The school also clinched the 2003 National Hopeful School Award for the Interior Schools Category in the country. In 2007, the school received the Education Ministry's Excellent School and Quality Award. Incredibly, the school's project on 'Community Participation in Achieving Quality Education in Difficult Circumstances' bagged the prestigious 2009 Commonwealth Education Good Practice Gold Award. In order to answer the four research questions put forward in this study, a research strategy which described the phenomenon in totality had been undertaken. In this regard, a qualitative case study had been adopted. In order to ensure the quality of data collected from the Head Teacher, other participants consisting of teachers, non-teaching staff, parents and community members were involved. They were specifically chosen as they would have personal experience of their Head Teacher's leadership and practical efficiency. They had been and were participating in the transformation of this school so in terms of their eligibility, they were the most appropriate choice to ensure the credibility of the data in the study. In this study, the Process Enneagram had been used as a guide for collecting data through interviews. According to Knowles (2002), the developer of Process Enneagram, leadership is an activity so it needs to be studied with a guide that reveals the activity components. Triangulation of the data collected was established through observations and document analysis. Based on the findings, six main leadership practices had contributed to the Head Teacher’s success in turning around the failing school: vision and goals; instructional leadership; administration and management; beliefs, values and attitudes; communication and linkages; and emotional engagement. These leadership practices and their interrelationships were depicted in the creation of SOLe (Self-Organizing Leadership for excellence) Framework which is the novelty of this study. One of the major conclusions of this case study was that the Head Teacher had played an effective role of bringing the community to the school and this had contributed greatly to the school's success. The implication was that effective school leadership did matter. It was found that this award winning Head Teacher had shaped the school through his synergistic power of leadership.